Respostas

2014-05-19T19:56:59-03:00
Equação do segundo grau com números antes da letra (incógnita) mudará poucas coisas nas formulas

4x^2+9=12x \\  \\ 4x^2-12x+9=0 \\  \\  \\ D=b^2-4.a.c \\  \\ D=(-12)^2-4.4.9 \\  \\ D=144-144 \\  \\ D=0


 \frac{-b+/- \sqrt{D} }{2.a}  \\  \\  \\ x'= \frac{-(-12+ \sqrt{0} )}{2.4} \>\>\>\>\>\>\>\>x'= \frac{12}{8}\>\>\>\>\text{simplificando por 4}\>\>\>\>\>\>\>\>x'= \frac{3}{2}  \\  \\ x"= \frac{-(-12)- \sqrt{0} }{2.4} \>\>\>\>\>\>\>\>x"= \frac{12}{8}\>\>\>\>\text{simplificando por 4 } \>\>\>\>x"= \frac{3}{2}